Vertebral-carotid transposition can treat various diseases - Yuanrui Gu (Vascular Investigation and Therapy, 2020)
Vertebral-carotid transposition (VCT), which is a treatment of vertebral artery stenosis, has excellent long-term efficacy. VCT can also be suitable for various situations where the blood supply of the vertebral artery must be reconstructed. Here, we present an early result of six cases for these anomalies by VCT. Case 1: A 58-year-old male presented with the severe stenosis at the left vertebral V1 segment. Case 2: A 59-year-old female suffered from moderate-to-severe stenosis at the first portion of the left subclavian artery. Case 3: A 55-year-old female experienced severe stenosis at the left vertebral V1 segment, which the wire could not pass through. Case 4: A 53-year-old female presented with the subclavian aneurysm at the origin of the right vertebral artery. Case 5: A 65-year-old male suffered from the long complete occlusion at the origin of the left subclavian artery, a severe stenosis at the origin of the left internal carotid artery, a severe stenosis at the origin of the right internal carotid artery, and a severe stenosis at the right vertebral V1 segment. Case 6: A 56-year-old male experienced the thrombus in the stent of the vertebral artery which had been placed 6 months ago. There are six cases, in which VCT was adapted. VCT is safe and effective for various situations when the blood supply of the vertebral artery must be reconstructed.